The development of mobileand Internet-based payment services as factors offinancial accessibility improvement - S. V. Kryvoruchko; Tung Tchan Son (Путеводитель предпринимателя, 2020)
The article describes the options of mobile technology in financial services which reduce operating costs, risks, expand coverage and use of microfinance institutions (MFIs) products. Mobile operators offer mobile banking services that allow MFIs to build a technological platform for the transfer offunds. One of the pilot projects in this area is M-Pesa in Kenya.